The Influence of Farm Characteristics and Feed Compositions on the Environmental Impact of Pig Production in Flanders: Productivity, Energy Use and Protein Choices Are Key - Klara Van Mierlo (MDPI AG, 2021)
The growing pig production sector is a large contributor of negative impacts to the environment and feed production is responsible for a large part of these impacts. Pig production systems, including feed compositions, are variable, resulting in variable potential environmental impacts. This study investigated the influence of different farm characteristics and feed compositions on the environmental impact of pig production in Flanders. A Life Cycle Assessment approach was followed, including data from 39 farms and monthly feed compositions in the year 2018. Even though feed production contributes significantly to the overall environmental impact of pig production, the results show that environmental impacts are more affected by variabilities in farm characteristics than by fluctuating feed compositions. A higher productivity, in terms of feed conversion efficiency and the number of pigs produced per sow, is generally related to lower environmental impacts. Another influencing factor is the type and amount of energy used. For feed consumption, high variabilities are observed for water use, mainly caused by varying levels of sugar cane molasses. Climate change impacts and variabilities are mainly caused by soy ingredients and their origin. Finally, amino acids show large contributions to the environmental impact of pig feed consumption. Our research highlights that future developments for reducing the environmental impact of pig production should target animal productivity, the type and amount of energy used and selection of protein sources in pig feed.